1997
DOI: 10.1523/jneurosci.17-14-05573.1997
|View full text |Cite
|
Sign up to set email alerts
|

Adrenergic Receptors in Alzheimer’s Disease Brain: Selective Increases in the Cerebella of Aggressive Patients

Abstract: In this study, the distribution and concentration of ␤ 1 , ␤ 2 , and ␣ 2 adrenergic receptors were examined in the frontal cortex, hypothalamus, and cerebellum of Alzheimer's disease (AD) and age-matched control human brains by receptor autoradiography. The purpose of this study was to detect changes in adrenergic receptor concentrations in key areas of the brain known to affect behavior. For these studies, 3 H]UK-14,304 was used to localize the ␣ 2 sites. Essentially no significant difference in adrenergic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(42 citation statements)
references
References 39 publications
2
39
0
1
Order By: Relevance
“…This differential impact is consistent with prior studies indicating that cognitive performance can be improved in rodents independently of aggression [57,58]. Similarly, while both cognitive impairment and aggression accompany AD, they are not necessarily temporally colocalized and may but do not necessarily respond to identical treatments [59][60][61][62]. These behavioral manifestations in mice are directly relevant since AD can be accompanied by psychosis and agitation [63], and ApoE4 can also potentiate psychotic symptoms in humans [64].…”
Section: Nutritional Deficiency Potentiates the Impact Of Deficiency supporting
confidence: 86%
“…This differential impact is consistent with prior studies indicating that cognitive performance can be improved in rodents independently of aggression [57,58]. Similarly, while both cognitive impairment and aggression accompany AD, they are not necessarily temporally colocalized and may but do not necessarily respond to identical treatments [59][60][61][62]. These behavioral manifestations in mice are directly relevant since AD can be accompanied by psychosis and agitation [63], and ApoE4 can also potentiate psychotic symptoms in humans [64].…”
Section: Nutritional Deficiency Potentiates the Impact Of Deficiency supporting
confidence: 86%
“…36 Regarding the adrenergic system, it has been shown that patients with AD who display aggressive behaviors have a markedly higher level of ␣ 2 , ␤ 1 , and ␤ 2 adrenergic receptors in the cerebellar cortex. 37 There is also a relative preservation of inhibitory noradrenergic neuronal input to the cerebellar cortex (tyrosine hydroxylasepositive neuronal fibers) in patients with AD who exhibit aggressive behavior. 38 Regarding the serotoninergic system, loss of serotonin 2 (5-HT 2 ) receptors in multiple cortical areas 39 and reduced density of 5-HT 1A receptors in temporal areas 40 has been reported for patients with AD who manifest aggressive behavior.…”
Section: Commentmentioning
confidence: 99%
“…α 2 -Adrenergic receptors have been reported as either unaltered [402] or reduced [403][404][405] in frontal cortex of Alzheimer patients. However, the preservation or decrease of α 2 -adrenergic receptors in brain tissue occurs in spite of a large increase in α 2 -adrenergic receptors in cerebral microvessels [406].…”
Section: Alzheimer's Diseasementioning
confidence: 99%
“…Accordingly the density of parenchymal α 2 -receptors must be decreased. Available evidence regarding other noradrenergic receptors is less consistent [402,[407][408][409]. MAO B increases during normal aging, but is overexpressed in Alzheimer's brains, compared to agematched controls [410][411][412], at least partly reflecting that MAO B is associated with fibrillary astrocytes in and around amyloid plaques [413].…”
Section: Alzheimer's Diseasementioning
confidence: 99%